Sensitive label-free immunoglobulin G detection using a MEMS quartz crystal microbalance biosensor with a 125 MHz wireless quartz resonator. (29th March 2021) - Zhou, Lianjie; Kato, Fumihito; Ogi, Hirotsugu
Abstract: We present a wireless quartz crystal microbalance (QCM) biosensor fabricated using MEMS technology. The MEMS QCM biosensor contains a 125 MHz AT-cut quartz resonator embedded in the microchannel. Because of the compact design, the MEMS QCM biosensor is suitable for mass production and device miniaturization. We performed immunoglobulin G (IgG) detection measurements with different concentrations of IgG. The detection limit was 1 ng ml –1 or less, which is superior to that of the gold-standard surface plasma resonance method. Furthermore, we studied the binding affinity between protein A and IgG by studying the frequency response of the QCM biosensor. We found good agreement with reported values. Therefore, the presented MEMS QCM biosensor has the advantages of compactness, low cost, low power consumption, high sensitivity, and reliability.